Surfing Tourism Marketing Communication Through the "Bengkulu Surf Instagram" Account As a Promotional Media - Rahman Dwivan; Vethy Octaviani; Sapta Sari (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
This study aims to determine the role of the Bengkulu Surf Instagram account as a promotional medium in increasing surfing tourism at Tapak Paderi Bengkulu City. The purpose of this study was to find out Marketing Communication for Surfing Tourism Through Bengkulu Surf Instagram Accounts as a promotional medium (Studies on Surfing Tourism IG Accounts in Tapak Paderi Bengkulu City). The type of research used in this research is a research study with a qualitative descriptive approach. Based on the results of the study, it can be concluded that the Bengkulu Surf account has used promotions through Instagram social media by utilizing Instagram features related to promotions (poromotion mix) in the form of addeveritising (advertising), public relations (public relations), sales promotion (sales) and personal selling (personal selling) maximize the promotion. Having features on Instagram adds to the advantage of promoting the @bengkulusurf account because it's easier and more efficient. This proves that Instagram is an online social media that is very appropriate in carrying out promotional activities.